2012
DOI: 10.1111/j.1365-2958.2012.08047.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular aspects of the distinct M protein and SfbI anchoring pathways in Streptococcus pyogenes

Abstract: Summary Wall-anchored surface proteins are critical for the in vivo survival of Streptococcus pyogenes. Cues in the signal sequence direct the membrane translocation of surface proteins: M protein to the septum, and SfbI to the poles. Both proteins are subsequently anchored to the wall by the membrane bound enzyme sortase A. However, the cellular features of these pathways are not fully understood. Here we show that M protein and SfbI are anchored simultaneously throughout the cell cycle. M protein is rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 73 publications
2
28
0
Order By: Relevance
“…Furthermore, we showed the two major bands of the M protein from the digestion of these ΔsagA and wild-type GAS bacteria with the phage lysin PlyC 27 in western blots. The blotting pattern is the same with that in the study of Raz et al, 28 which used the PlyC treatment to release the M protein from the cell wall, and the M protein band with the higher molecular weight was an indication of the M protein linkage to the residual moiety of the peptidoglycan. Thus, the M protein produced in strains of MGAS2221ΔsagA-3, MGAS2221ΔsagA-4, and MGAS5005ΔsagA was full-length and linked to the peptidoglycan.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, we showed the two major bands of the M protein from the digestion of these ΔsagA and wild-type GAS bacteria with the phage lysin PlyC 27 in western blots. The blotting pattern is the same with that in the study of Raz et al, 28 which used the PlyC treatment to release the M protein from the cell wall, and the M protein band with the higher molecular weight was an indication of the M protein linkage to the residual moiety of the peptidoglycan. Thus, the M protein produced in strains of MGAS2221ΔsagA-3, MGAS2221ΔsagA-4, and MGAS5005ΔsagA was full-length and linked to the peptidoglycan.…”
Section: Discussionsupporting
confidence: 58%
“…In a pioneer study in Streptococcus pyogenes, Carlsson et al demonstrated that the signal sequence of M protein, which contains an YSIRK-G/S motif (SP +YSIRK ), is targeted to the division septum, while the signal sequence of protein F (PrtF, also known as SfbI) lacking this motif (SP ÀYSIRK ) is targeted to the old pole [43 ]. Recently, Raz et al confirmed the differential localization of M protein and PrtF/SfbI in S. pyogenes and further provided a dynamic 3D view of protein localization during cell cycle [49 ]. M protein is rapidly anchored at the septum, simultaneously at the mother and daughter septa.…”
Section: Current Opinion In Microbiologymentioning
confidence: 82%
“…In a study of the localization of wall-anchored proteins in S. pyogenes, Raz et al noted that methicillin treatment at precisely 0.2 mg/ml induced coccus to rod transition. 20 This observation is counterintuitive as S. pyogenes does not encode for the elongation proteins PBP2b, RodA, MreC, and MreD (Table 1). Methicillin is known to inhibit specifically PBP2x in ovoid bacteria such as S. pneumoniae 12 and L. lactis.…”
mentioning
confidence: 99%